Community-Acquired Pneumonia in Elderly Patients - Artanti, Mariesela; Soleha, Tri Umiana; Nareswari, Shinta (PT. Riset Press International, 2025)
Community-acquired pneumonia (CAP) is a lung infection acquired outside of healthcare facilities and is a leading cause of morbidity and mortality in the elderly. Older adults have a higher risk of CAP due to immune system decline, comorbidities, and impaired respiratory defence mechanisms. Streptococcus pneumoniae is the primary pathogen responsible for CAP in the elderly, followed by Haemophilus influenzae and other atypical bacteria. The diagnosis of CAP in older adults is often challenging due to atypical symptoms such as general weakness and confusion, necessitating chest radiography for confirmation. Treatment depends on disease severity and may involve oral or intravenous antibiotics, oxygen therapy, and close monitoring for complications such as respiratory failure and sepsis. Prevention through pneumococcal and influenza vaccination, personal hygiene maintenance, and management of comorbidities is crucial in reducing CAP incidence and mortality in the elderly.